Velociraptors - Emmons, Scott; Ilic, Nikolas; Netflix (Firm); Random House Children's Books (New York Random House, 2021)
The StoryBots tell you about velociraptors
"A science reader"--Cover
"Netflix. A Netflix original series"--Cover
At head of title: StoryBots
English Stories
Preschool-Kindergarten
F&P text level: G
Keywords: Dinosaurs -- Juvenile fiction; Readers (Primary); Stories in rhyme; Velociraptor -- Juvenile fiction; Dinosaurs; Readers; Velociraptor; Dinosaurs; JUVENILE FICTION / Animals / Dinosaurs & Prehistoric Creatures; Readers (Primary); Velociraptor; Juvenile works; Readers (Publications); Readers (Publications)